Terengganu's tourism industry: an analysis of its competitiveness from 1996 to 2020 / Noor Zatul Iffah Hussin ... [et al.] - Hussin, Noor Zatul Iffah; Mohd Fuza, Zatul Iffah; Padlee, Siti Falindah; Ismail, Fathilah; Ismail, Roslina (Universiti Teknologi MARA, Terengganu, 2024)
This study investigates the effectiveness of the Terengganu plan by focusing on economic growth in Terengganu from 1996 to 2020, with a particular focus on tourist arrivals, receipts, workforce development, and contributions to gross domestic product (GDP). This study is limited to 2020 because each time frame of the plan spans five years. The current plan is not yet complete, which is why this study is limited to the year 2020. The introduction highlights the significance of the tourism sector as a key driver of Terengganu's economy, with a strong emphasis on nature-based and cultural heritage tourism offerings. A qualitative content analysis methodology is employed, using secondary data from government reports from the Terengganu Economic Planning Unit and the Terengganu Town and Country Planning Department. This method enables a thorough examination of how promotion strategies have shaped the tourism landscape. The results reveal that tourism has significantly contributed to economic growth through increased tourist arrivals, higher revenue generation, and job creation. Successful initiatives, such as the “Visit Terengganu” promotional campaign, are recognized as contributing factors. The research concludes that while tourism policies have been effective in fostering growth, further improvements are needed to ensure sustainable development and maintain the competitiveness of Terengganu's tourism industry in the long term.